Migration impact on left-behind Elderly’s labour participation in Kerala - V.P. Sanitha AND A.P. Noushad (Indian Journal of Economics and Development, 2018)
Objectives: An attempt was made to study the migration impact on left-behind Elderly’s labour force participation in Kerala. Methodology: This paper was entirely based on secondary data sources collected from various reports such as census of India, Kerala migration survey reports, economic review of Kerala etc. Correlation matrix has been used to find out the relationship between remittances and WPR of elderly among the districts in Kerala. Findings: Migration not only reduces the number of potential care givers within the family, but it also result in a deterioration of the quality of family support and consequently to an annoyance of the elderlies' well-being and health conditions and also reduces the labour market participation of left-behind elderly. There is a negative correlation between international migration and the work participation of the left behind elderly members. Districts that account for higher rates of emigration show low levels of elderly participation in the labour market and vice versa. Application/Improvement: The study suggested for taking the actions to alleviate the financial over dependence, ensure social security measures for the aged and the increased role of government in taking care of the aged. If the government is not taken any steps towards the aged now, it will become very difficult to provide proper care and security to the elderly people in the coming decades.